An analysis of hemoglobin levels and body fat percentage on leg power in volleyball athletes - Fauzi; Handaka, Riky Dwi; Majid, Nur Cholis; Miftachurochmah, Yulvia (SPORT TK-EuroAmerican Journal of Sport Sciences, 2025)
This study aimed to determine the possible relationship between fat percentage and hemoglobin levels on leg power levels. It employed an analytical observational design using a cross-sectional approach. The sampling technique applied was purposive sampling, with the sample studied involving 24 male volleyball athletes aged under 22 years. Hemoglobin was assessed using the cyanmethemoglobin method. Body fat percentage was measured using Bioelectrical Impedance Analysis with the Omron Karada Scan HBF-358, while leg power was evaluated using the vertical jump test. The results indicated a strong negative relationship between the percentage of body fat and leg power (p=0.002; r=-.610), and a strong positive relationship between hemoglobin levels and leg power (p=0.001; r=0.613). The study demonstrated that a higher body fat percentage is associated with high power levels. In contrast, elevated hemoglobin concentrations are also positively related to power, indicating that both oxygen-carrying capacity and body composition may influence muscular performance.